Analysis of the Implementation of the National Paralympic Committee of Indonesia Swimming Training Program in 2021 - Rahman, Syahrizal Emil (Journal of Physical Education Health and Sport, 2021)
The Covid-19 pandemic canceled and postponed several sports events so that the targets that had been prepared and planned in the National Paralympic Committee training program were neglected. The purpose of this research is to describe the strengths, weaknesses, opportunities, and threats in the implementation of the training program at the National Paralympic Swimming Committee Indonesia 2021. These studies use a qualitative descriptive method. The research subjects were Head coaches, coaches, athletes, and administrators of the National Paralympic Committee. The data analysis technique includes data collection, data reduction, data presentation, and data conclusion. The validity of the data in this study used data triangulation. Research result. 1) Strength: the implementation of the mesocycle, microcycle, macrocycle training program, the complete composition of trainers and infrastructure affects strength in the implementation of the swimming training program at the National Paralympic Committee. 2) weakness: targets on training programs that have been neglected due to the pandemic have made sports events canceled so that the training programs are not on target. 3) opportunity: the implementation of the National Paralympic Committee swimming training program brings achievement opportunities for athletes with Tryout Results who have reached the target. 4) The delay of several events can affect the athlete's mental state so that it poses a threat to the athlete during the competition. The recommendation from the results of the SWOT analysis is that the Swimming training program at the National Paralympic Committee has been measured and structured based on existing training theory. Although the targets in the training program had not been realized due to the Covid-19 pandemic, it is hoped that the National Paralympic Committee's Swimming athletes and coaches can prepare the athlete's condition for the upcoming event. So that athletes can readjust mentally back to the next competition.